2008
DOI: 10.1080/01411920802223974
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and performativity: The case of further education

Abstract: This article examines the circumstances affecting creative teaching and learning within the specific context of English further education (FE)—a sector which has proved to be particularly fertile ground for performativity. Beginning with an analysis of notions of creativity in education and a description of the peculiar history and policy context of FE, the article problematises the relationship between representations of creativity and the current situation of teachers and learners. Drawing on a range of empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 36 publications
1
45
1
Order By: Relevance
“…Although this was over forty years ago, this may still be an issue as Fryer and Collings (1991) reported that research into teachers' views of creativity has been somewhat neglected and Simmons and Thompson (2008) have more recently commented on tensions surrounding creativity in education, one being the difficulty of defining it.…”
Section: )mentioning
confidence: 99%
“…Although this was over forty years ago, this may still be an issue as Fryer and Collings (1991) reported that research into teachers' views of creativity has been somewhat neglected and Simmons and Thompson (2008) have more recently commented on tensions surrounding creativity in education, one being the difficulty of defining it.…”
Section: )mentioning
confidence: 99%
“…In contrast, FE is today replete with rhetoric about the supposed importance of pedagogy. But whilst such notions are rooted, at least partly, in certain discourses of creativity and the demands of the so-called knowledge economy (Simmons and Thompson, 2008), LS/GS teachers were often at the forefront of classroom innovation, and pioneered student-centred learning in FE. Lorraine: What I thought was most worthwhile was .…”
Section: Student-centred Learningmentioning
confidence: 99%
“…Menken (2006:525) coined the term 'teach to test' to express the notion of primarily educating students to pass exams, with little emphasis on developing skills such as creativity. Simmons and Thompson (2008) argued that the expression of creativity allows teachers and learners to escape the narrow confines of the centralised curricula, but that the independence of teachers has been reduced by the overwhelming pressure to meet targets. In contrast, other researchers have suggested that the inclusion of creative polices alongside performance-driven criteria, such as targets, market competition and league tables, increases levels of tension for those learning and teaching (Ball, 2003;Jeffrey, 2003;Troman et al, 2007b).…”
Section: 'Teach To Test' and Creativitymentioning
confidence: 99%